(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Micro and small enterprises (MSEs) face chronic working-capital frictions that cascade to consumers as stockouts, delivery slippage, and limited payment options. This study reframes entrepreneurial finance as an upstream lever shaping consumer outcomes via two mechanisms reliability/trust and payment flexibility. A synthetic panel of 20 firms observed monthly for 24 months (480 firm-months) is analysed using staggered difference-in-differences with firm and month fixed effects, event-study diagnostics, and sequential mediation; inference is cluster-robust at the firm level. Supplier-finance adoption reduces stockouts by 4.44 percentage points and increases on-time fulfilment by 3.75 points, translating into a 2.89-point rise in repeat purchase and a +3.50-point trust/reliability index. Buy Now Pay Later (BNPL) availability raises conversion by 2.31 percentage points and average order value by ₹44. Mediation indicates a sizable reliability pathway from supplier finance to repeat (indirect ≈ +0.020) and a minimal liquidity pathway; BNPL effects operate through payment-flexibility gains. An interaction shows smaller BNPL conversion lifts where institutional quality is higher. Results are robust to sector×month and city×month controls, winsorisation, and placebo timing. The contribution is twofold: positioning financing as market design in consumer research and quantifying mechanism-linked effects under modern identification. Managerial guidance emphasises sequencing stabilise availability, then expand payment flexibility supported by credit-management and fulfilment analytics. Limitations include synthetic data and proxy measures; future work should validate on administrative datasets and integrate consumer credit-health outcomes.